2010
DOI: 10.1177/1553350610387616
|View full text |Cite
|
Sign up to set email alerts
|

Selective Embolization of Thyroid Arteries for Preresection or Palliative Treatment of Large Cervicomediastinal Goiters

Abstract: Selective embolization of thyroid arteries can be successfully used to treat selected patients as a preoperative procedure and as an alternative to thyroid resection. Embolization can be repeated to achieve the required therapeutic aims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Like 'operative time', this variable affects the overall costs of the procedure, although this is due not so much to the method used as to the possible onset of postoperative hypocalcaemia, which can arise even as long as 48–72 h after the surgery, especially in hyperfunctioning goitres. In addition, the length of hospital stay varies according to local practices: the US authors, generally accustomed to short stays, habitually discharged their patients 24 h after TOETVA or MIVAT, whereas in the Asian and European studies hospital stays were prolonged beyond the 2 nd day, probably to monitor the levels of post-operative calcaemia;[ 40 41 42 43 44 45 46 47 48 49 50 51 52 ] this is indeed in line with our practice.…”
Section: Discussionsupporting
confidence: 68%
“…Like 'operative time', this variable affects the overall costs of the procedure, although this is due not so much to the method used as to the possible onset of postoperative hypocalcaemia, which can arise even as long as 48–72 h after the surgery, especially in hyperfunctioning goitres. In addition, the length of hospital stay varies according to local practices: the US authors, generally accustomed to short stays, habitually discharged their patients 24 h after TOETVA or MIVAT, whereas in the Asian and European studies hospital stays were prolonged beyond the 2 nd day, probably to monitor the levels of post-operative calcaemia;[ 40 41 42 43 44 45 46 47 48 49 50 51 52 ] this is indeed in line with our practice.…”
Section: Discussionsupporting
confidence: 68%
“…In Graves, the incidence varies from 0.5% to 1.8% (45)(46)(47)(48)(49). The incidence of carcinomas in the cervicomediastinal goiter compared with benign thyroid cervical-mediastinum disease, is around 12.1% (50,51). The association with parathyroid diseases (52)(53)(54)(55)(56) and lymphocytic thyroiditis (57, 58) is also described.…”
Section: Discussionmentioning
confidence: 99%
“…We found that ipsilateral thyroid reduction was obtained in all patients, and the mean volume reduction was 50.0% ± 15.9% at the 3‐month follow‐up. The effect was not inferior to that obtained by selective embolization of thyroid arteries …”
Section: Discussionmentioning
confidence: 60%
“…The effect was not inferior to that obtained by selective embolization of thyroid arteries. 26 Compressive symptoms and cosmetic problems resolved in all patients after MWA. In this study, we intended to achieve symptom relief in patients with SSG; therefore, only patients with of associated symptoms were recruited.…”
Section: Discussionmentioning
confidence: 85%